Synthesis, characterization and in situ bioefficacy evaluation of Cymbopogon nardus essential oil impregnated chitosan nanoemulsion against fungal infestation and aflatoxin B1 contamination in food system - Prasad J.; Das S.; Maurya A.; Jain S.K.; Dwivedy A.K. (My University, 2025)
The present investigation aimed to synthesize Cymbopogon nardus essential oil impregnated chitosan nanoemulsion (Ne-CNEO) and its practical efficacy as novel green delivery system for protection of Syzygium cumini seeds against broad range storage fungi, aflatoxin B1 (AFB1) secretion and lipid peroxidation. Chemical characterization of CNEO revealed citral (62.73%) as major component. Successful impregnation of CNEO inside chitosan nanoemulsion was confirmed through SEM, AFM and FTIR analyses. In vitro release study showed biphasic release profile with initial burst followed by sustained release of CNEO from chitosan nanomatrix. Ne-CNEO exhibited enhancement in in vitro antifungal, antiaflatoxigenic (0.16 μL/mL) and antioxidant activity over CNEO. The antifungal and antiaflatoxigenic mechanism of action of Ne-CNEO was associated with inhibition of ergosterol biosynthesis, increased leakage of cellular contents, and impairment in cellular methylglyoxal biosynthesis. In silico modeling validated interaction of citral with Ver-1 and Omt-A proteins, confirming the molecular action for inhibition of AFB1 production. In situ investigation suggested remarkable protection of S. cumini seeds against fungal inhabitation, AFB1 production and lipid peroxidation without affecting organoleptic attributes. Furthermore, higher mammalian non-toxicity strengthens the application of Ne-CNEO as safe nano-green and smart preservative in place of adversely affecting synthetic preservatives in emerging food, agriculture and pharmaceutical industries. © 2022 Elsevier B.V.